2022
DOI: 10.1371/journal.pone.0276422
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ghanaian nurses knowledge and application of bio-ethical principles in postoperative pain management

Abstract: Managing postoperative pain require good understanding of the bio-ethical principles in order to preserve patients’ rights. Bio-ethical principles in health care include autonomy, beneficence, justice and nonmaleficence. It is important that health care professionals understand that patients in pain have the right to satisfactory management. Good insight on ethical principles and how they relate to pain management places the nurse on a better pedestal to manage postoperative pain effectively. However, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The research conducted by Pathman et al ( 2022 ) and Ulrich et al ( 2014 ) demonstrated that American nurses (44%) possess a high level of moral readiness and confidence, which resulted in a low level of moral distress. On the other hand, lower-income countries in sub-Saharan Africa, such as Ghana (Tia et al, 2022 ), Ethiopia (Miljeteig et al, 2019 ), Tanzania (Aboud et al, 2014 ), and Nigeria (Ulrich et al, 2010 ), nurses experienced moral distress in moderate to high levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research conducted by Pathman et al ( 2022 ) and Ulrich et al ( 2014 ) demonstrated that American nurses (44%) possess a high level of moral readiness and confidence, which resulted in a low level of moral distress. On the other hand, lower-income countries in sub-Saharan Africa, such as Ghana (Tia et al, 2022 ), Ethiopia (Miljeteig et al, 2019 ), Tanzania (Aboud et al, 2014 ), and Nigeria (Ulrich et al, 2010 ), nurses experienced moral distress in moderate to high levels.…”
Section: Introductionmentioning
confidence: 99%
“…Differing cultural backgrounds can impact moral practices and standards in healthcare (Wright et al, 1997 ). Therefore, to deliver moral and individualized care, nurses are encouraged to incorporate the patient and family’s cultural beliefs, values, and needs into their nursing practice (Tia et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing competency requires providing safe and high-quality nursing care by ethical principles. These ethical principles in nursing can be ranked as autonomy, beneficence, nonmaleficence, veracity, confidentiality, justice, and fidelity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%